Multi-day, multi-sensor ambulatory monitoring of gastric electrical activity. (28th February 2019) - Paskaranandavadivel, Niranchan; Angeli, Timothy R; Manson, Tabitha; Stocker, Abigail; McElmurray, Lindsay; O'Grady, Gregory; Abell, Thomas; Cheng, Leo K
Abstract: Objective : Bioelectrial signals known as slow waves play a key role in coordinating gastric motility. Slow wave dysrhythmias have been associated with a number of functional motility disorders. However, there have been limited human recordings obtained in the consious state or over an extended period of time. This study aimed to evaluate a robust ambulatory recording platform. Approach : A commercially available multi-sensor recording system (Shimmer3, ShimmerSensing) was applied to acquire slow wave information from the stomach of six humans and four pigs. First, acute experiments were conducted in pigs to verify the accuracy of the recording module by comparing to a standard widely employed electrophysiological mapping system (ActiveTwo, BioSemi). Then, patients with medically refractory gastroparesis undergoing temporary gastric stimulator implantation were enrolled and gastric slow waves were recorded from mucosally-implanted electrodes for 5 d continuously. Accelerometer data was also collected to exclude data segments containing excessive patient motion artefact. Main results : Slow wave signals and activation times from the Shimmer3 module were closely comparable to a standard electrophysiological mapping system. Slow waves were able to be recorded continuously for 5 d in human subjects. Over the 5 d, slow wave frequency was 2.8 ± 0.6 cpm and amplitude was 0.2 ± 0.3 mV. Significance : A commercial multi-sensor recording module was validated for recording electrophysiological slow waves for 5 d, including in ambulatory patients. Multiple modules could be used simultaneously in the future to track the spatio-temporal propagation of slow waves. This framework can now allow for patho-electrophysiological studies to be undertaken to allow symptom correlation with dysrhythmic slow wave events.